2015
DOI: 10.1177/0020764015607919
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal depression in coastal South India: Prevalence and risk factors in the community

Abstract: There is a need to develop strategies for recognition and appropriate intervention for antenatal depression, in the context of locally relevant risk factors, so as to improve both maternal and child outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 35 publications
8
48
3
1
Order By: Relevance
“…The prevalence of antenatal depression in China (participants aged 20 to 35 years) and coastal South India (participants aged 19 to 44 years) was very similar at 13.7% and 16.3%, respectively [40,41]. However, the prevalence of 15.9% for antenatal (during pregnancy) depression that was observed for our sample of participants was lower than the prevalence of 38.5% reported in a study in Durban, KwaZulu-Natal [34].…”
Section: Discussioncontrasting
confidence: 54%
“…The prevalence of antenatal depression in China (participants aged 20 to 35 years) and coastal South India (participants aged 19 to 44 years) was very similar at 13.7% and 16.3%, respectively [40,41]. However, the prevalence of 15.9% for antenatal (during pregnancy) depression that was observed for our sample of participants was lower than the prevalence of 38.5% reported in a study in Durban, KwaZulu-Natal [34].…”
Section: Discussioncontrasting
confidence: 54%
“…The reported prevalence of antenatal depression is around 20% in Asian countries and 15.6% in LMICs 50,51 . Our results concur with evidence from other parts of India 52 . Given that we have shown the probable association with SGA, as do earlier studies in India and elsewhere, there is a need for policymakers to prioritize screening pregnant women for mental health problems.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies had reported that antenatal depression was significantly associated with age [20], unplanned pregnancy [21], smoking during pregnancy, history of abortion and stillbirth, presence of a complication in the current pregnancy, previous history of depression, low educational attainment, and irregular menstrual history [17,[22][23][24]. Besides, domestic violence, financial stress, history of miscarriage, marital conflict, and drinking alcohol during pregnancy were significant predictors of antenatal depression [4,25,26].…”
Section: Introductionmentioning
confidence: 99%